Detection of Extended Spectrum ?-Lactamase Producing Bacteria in Combined Military Hospital, Dhaka - Hoque, MM; Ahmad, M; Chowdhury, JP; Nurunnobi, S; Mahmood, S (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i2.16341 JAFMC Vol.8(2) 2012 pp.08-15